O jogo como método facilitador no ensino e aprendizagem dos polígonos regulares - Santos, Raimunda Maria Souza dos (Brasil, 2023)
This monographic work of conclusion of course, has as main objective to present the study of the regular polygons, through concrete games. Studies and research show us that educational practice has undergone several changes in the educational field. However, the indicators from the external evaluations present us with very low data focused on the area of mathematics. These data increasingly confirm that school failure is reflected in student learning, requiring something from teachers that can go beyond traditional classes and appropriate pleasurable practices to improve student learning in the teaching of regular polygons